The threat of a major tree pathogen to forest soil mesofauna food webs and ecosystem functioning - Struijk, Marijke; Stavert, Jamie R.; Le Grice, Rebecca J.; Schwendenmann, Luitgard; Romera, Poppy Joaquina; Mitchell, Grace; Sünnemann, Marie; Yang, Jaynie; Hjelm, Fredrik; Barnes, Andrew D. (Frontiers in Ecology and Evolution, 2024)
Tree pathogens threaten the survival of many forest foundation tree species worldwide. However, there is limited knowledge of how dieback of foundation tree species may threaten other components of forest ecosystems, such as soil biodiversity and associated ecosystem functions. Kauri (Agathis australis), threatened by the root-borne pathogen Phytophthora agathidicida, are culturally and ecologically significant tree species that exert great influence on soil properties. We aimed to characterise soil mesofauna community structure and energy fluxes in kauri forests and assess the potential threat that tree pathogens such as P. agathidicida pose to belowground ecosystems. We sampled soil mesofauna communities and identified specimens to functional feeding groups at 24 pairs of kauri and adjacent broadleaf trees in sites across the Waitākere Ranges Regional Park, Aotearoa -New Zealand. We attributed kauri canopy health scores, measured tree diameter, slope, forest floor depth, and soil carbon dioxide efflux. We also analysed soil samples for P. agathidicida presence, total carbon, and total nitrogen. We constructed soil mesofauna food webs associated with kauri and broadleaf trees, and assessed the uniqueness of food webs associated with kauri and the impacts of P. agathidicida on density, biomass, mean body mass, and energy fluxes of mesofauna taxonomic and trophic groups. We found omnivores with larger body mass at kauri where P. agathidicida was detected (i.e., P. agathidicida-positive soils). Compared to broadleaf trees, mesofauna density and biomass were lower in soils under kauri, and body masses of Symphyla and omnivores were smaller in soils under kauri. Differences in mesofauna community response variables between tree types were mainly modulated by the soil C:N ratio, which had positive effects under broadleaf and neutral to negative effects under kauri. Energy fluxes to detritivores and fungivores were greater under larger trees, regardless of tree type or P. agathidicida detection status. Our findings suggest that kauri support soil mesofauna food webs that are distinctly different from those found under broadleaf trees in the same habitat. A decreased presence of this foundation species may be linked to future impacts on soil mesofauna in this forest ecosystem with increasingly advanced stages of kauri dieback.